The transmutation modeling for plutonium and minor actinides in the two-zone subcritical reactor - Gulik, V.I.; Sheliahovskyi, D.O.; Nosovskyi, A.V. (Вопросы атомной науки и техники, 2019)
The investigations directed to plutonium and minor actinides transmutations for two-zone subcritical reactor is considered in present paper. The distributions of thermal and fast neutrons in the subcritical system were obtained. The distributions of fission and capture reaction rates for ²³⁷Np and ²⁴³Am were analyzed from viewpoint of minor actinides transmutation. The transmutation simulations for different distributions of pin targets were carried out within the scope of this paper. The obtained modeling results for different nuclear waste isotopes were analyzed and discussed.